Estrutura das comunidades de pequenos mamíferos de duas unidades de conservação (Taim e Espinilho) do bioma Pampa, Sul do Brasil - Sponchiado, Jonas (2011)
The small-mammal community structure of two conservation unit (CUs), Taim Ecological Station (TES) and Espinilho State Park (ESP), of the Pampa biome in southern Brazil, was investigated and compared regarding species richness, composition and abundance. Additionally, a Deciduous forest area was compared with those ones. For this purpose, ten transects with live-traps pitfall traps were used. In addition, sixteen environmental variables were measured in the TES to verify the small-mammal micro-spatial distribution. During six field phases in each area, 11 species were capture at TES, while nine species were captured in the ESP. The two areas of the Pampa biome showed high species richness when compared to forested areas, since both are influenced by other biomes: TES by the Atlantic Forest, as it is close to the coastal region, and the ESP by the interior of the continent biomes, Chaco and Espinal. The abundance and composition were different due to environmental heterogeneity, biogeography effect, size areas and degree of disturbance. However, environmental heterogeneity allows both areas to have similar species richness. When compared with the Atlantic forest CU, they differ in species richness, composition and abundance of individuals due to greater homogeneity and complexity of the forested area. With respect to the microspatial distribution, species richness and abundance were associated with sites close to water, with greater availability of arthropods and herbs. Since there is great variability of environments at TES, the heterogeneity is primarily responsible for the variation in richness and abundance of small mammals among microhabitats. The analysis indicated a significant effect of environmental variables on species abundance, showing the selection of some environments more often than others.